Les eaux comme frontières dans les Enfers gréco-romains, d’après L’Odyssée d’Homère, la Théogonie d’Hésiode, La République de Platon et L’Énéide de Virgile - Emilia Ndiaye (Frontière·s)
Waters are everywhere in the Ancient Netherworld, at the entrance and inside as several rivers organize the topography into various separate spaces. They represent a geographical border which, in Hesiod’s vertical organization of the world, marks the limit between the earthly surface of the living and the underworld of the dead: thus, in the Odyssey, the confluence of the two rivers, at the edge of the Ocean, marks the entrance to the Underworld for Ulysses, whereas it is the lake Avernus for Aeneas, in Virgil’s Aeneid; or the Styx and its marshes that the dead cross in Charon’s boat. Once in the realm of Hades, rivers demarcate different areas. The Pyriphelegeton, ‘river of fire’, encloses Tartarus, reinforcing the separation between the criminals locked up there and the others; the river Ameles in the plain of Lethe symbolizes a border between past and future, providing souls with the oblivion of their past life before their reincarnation, according to the Platonic myths of the Phaedo and the Republic. We will consider the different forms of border the infernal waters illustrate in these Ancient literary texts: symbolic borders whose fluidity conceals a fundamental ambiguity–water as an element symbolizes both life and death–, by creating separations but also allowing transitions and circulation, especially between real and imaginary worlds.